TRADITIONAL TREATMENT AND MANAGEMENT OF MAGIC DISTURBANCE USING BIDARA LEAVES IN LUBUK BUAYA KELURAHAN PADANG SARAI KECAMATAN KOTO TANGAH KOTA PADANG - Hafizhah Hamdah (SEMESTA: Journal of Science Education and Teaching, 2020)
This article aims to describe a model of treatment that utilizes plants (plant medicine) found in the Padang tradition, especially Lubuk Buaya and its surroundings. The method used in this research is a qualitative research method and is descriptive in nature with an interactive analysis model. The author concludes that in the medicinal tradition using plants that are assisted by smart people in the Lubuk Buaya community. This tradition has probably been going on from generation to generation. This can be proven by still using this method of treatment. Some traditions may have originated outside the Padang culture which entered into the tradition along with the association of the community with other communities. There is no definite basis (logic) regarding the treatment. Some of the reasons for doing treatment with plants and helping smart people, namely because of traditions / habits and the presence of mystical elements. Another logic is the logic of transition, which is to consider things that are on the help of the smart person. This logic is quite common.